The Determinants of Corporate Cash Holdings: Evidence from Japan - Ong, Hui Min (2014)
In this paper, we examine the determinants of cash holdings using dataset of Japanese firms by using a panel of 1441 firms from 2004 through 2013. Our analysis reveals that firms with higher cash holdings are smaller in size, with lower capital expenditure and hold less net working capital. In addition, we find that firms with larger cash reserves in our sample experience greater cash flow volatility and have better growth opportunities (proxy using market-to-book value ratio). Our results indicate firms in Japan hold cash for precautionary motive. This suggests firms in Japan hold cash for security purpose in the event of adverse events or shocks. When we include bank debt alongside other firm characteristics, we find that firms with more bank debt tend to hold lower cash holdings over our study period. The close bank-firm relationship is further examined by the ownership concentration of banks in ownership structure. Our results suggest that a firm’s reliance on bank debt, as the most important financing source, is declining over time. As a result, we suggest monopoly power of Japanese banks has weakened. Finally, we examine the relationship between cash holdings and ownership characteristics while controlling for other firm characteristics. We find that lower cash holdings are observed in firms that are considered to be dominated foreign ownership where higher cash holdings are observed in firms which ownership by corporation is more concentrated. As such, we do not find strong evidence that support argument of agency conflicts due to large cash reserves.